2011
DOI: 10.4028/www.scientific.net/amr.306-307.696
|View full text |Cite
|
Sign up to set email alerts
|

The Electrochemical Polymerization of Polypyrrole Microstructures in an Aqueous Solution of Dodecylbenzenesulfonic Acid

Abstract: Conducting polymer – polypyrrole (PPy) microstructures were fabricated in an aqueous solution of dodecylbenzenesulfonic acid (DBSA) by electrochemical polymerization. The study implied the concentration of DBSA had great effect on the morphologies and conductivities of PPy microstructures. At lower DBSA concentration (0.2M), no obvious microstructures were generated. Increasing DBSA concentration, some novel “chayote-like”, “flower-like” microstructures were obtained by modulating electrochemical conditions. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The results showed that the sludge dehydration efficiency of the cyclic polyamidine was outstanding. Wang et al prepared the polyamidine firstly through the aqueous solution polymerization of NVF with AN within China [ 8 ]. The properties of polyamidine were assessed in terms of charge density, viscosity, and flocculating effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the sludge dehydration efficiency of the cyclic polyamidine was outstanding. Wang et al prepared the polyamidine firstly through the aqueous solution polymerization of NVF with AN within China [ 8 ]. The properties of polyamidine were assessed in terms of charge density, viscosity, and flocculating effect.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results indicated that the starch-grafted polyamidine exhibited promising oil–water separation efficiency. However, the synthetic pathway for preparing cyclic polyamidine based on aqueous solution polymerization may lead to lower yields and unsatisfactory charge density of the corresponding product [ 8 , 10 ]. Water used in polymerization should be further treated to prevent environmental pollution.…”
Section: Introductionmentioning
confidence: 99%
“…To load a clinically sufficient quantity of drugs into PPy, an increased ion-doping capacity is required. A promising approach to give PPy increased capacity is through the creation of surface micro-and nanostructures [7,[15][16][17][18][19][20]. A nanowire network, produced through electrochemical polymerization of pyrrole on a gold electrode, helped to achieve a larger drug loading capacity in the study by Jiang et al [18].…”
Section: Introductionmentioning
confidence: 99%
“…This process involves potentiodynamic polymerization of pyrrole around hydrogen bubbles enwrapped by surfactant molecules, as described by Qu et al [15]. By applying this method and controlling polymerization conditions, defined microstructures of varying shapes and sizes can be created [16,17,19]. Bajpai et al [17] demonstrated the ability to create such PPy microcontainers to encapsulate fluorescein (FL) molecules.…”
Section: Introductionmentioning
confidence: 99%